Relevant documents of the security council of the United Nations - United Nations (Law of the Sea Bulletin, 2014)
At the 6865th meeting of the Security Council, held on 19 November 2012, in connection with the Council’s consideration of the item entitled “Maintenance of international peace and security”, the President of the Security Council made the following statement on behalf of the Council: